2004
DOI: 10.1021/jp0372993
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Thionin with DNA Strands:  Intercalation versus External Stacking

Abstract: We have investigated thionin in a glycerol/water glass bound to DNA quadruplexes and DNA duplexes with pressure-tuning hole-burning spectroscopy at 2 K. For free thionin as a reference we could identify the two tautomeric structures (imino and amino form) in the inhomogeneous absorption bands. The measurement of local compressibilities from the spectral hole shifts under pressure allowed the assignment of binding modes of thionin to the DNA strands. Thionin binds via external stacking to the dimeric hairpin qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…The mode of DNA binding of thionine was speculated previously to be intercalative [15][16][17][18] and we probed the same using fluorescence quenching experiments in presence of [Fe(CN) 6 ] 4− . Quenching experiments are straight forward and indicate the location of the bound molecules to be either on the outside or inside of the helix.…”
Section: Fluorescence Quenching and Intrinsic Viscosity Studies For Ementioning
confidence: 98%
See 1 more Smart Citation
“…The mode of DNA binding of thionine was speculated previously to be intercalative [15][16][17][18] and we probed the same using fluorescence quenching experiments in presence of [Fe(CN) 6 ] 4− . Quenching experiments are straight forward and indicate the location of the bound molecules to be either on the outside or inside of the helix.…”
Section: Fluorescence Quenching and Intrinsic Viscosity Studies For Ementioning
confidence: 98%
“…It was further suggested [17,18] that thionine exists in two different tautomeric forms and the amino form is intercalated while Biophysical Chemistry 148 (2010) 93-103 the imino form is not. Although these data provide somewhat contradicting data on the GC specificity of thionine binding to linear double stranded DNA a recent study [17] by pressure tuning hole burning spectroscopy has conclusively shown an external stacking mode of binding of thionine to quadruplex structures. Thus, although some structural data is available, the same is not conclusive and the thermodynamics of thionine binding to DNA is not yet elucidated.…”
Section: Introductionmentioning
confidence: 98%
“…Thionine, an easily available cationic phenothiazine dye, intercalates in linear DNA duplex [30] stabilized by p -p stacking interactions between the planar dyes and the nucleotides. Another stabilization factor is the H-bonds between the exocyclic amines and the sugar-phosphates [31].…”
Section: Hybridization Of Beacon Dna Probe and Itsmentioning
confidence: 99%
“…An obvious decrease in the redox peak currents for the Th-NWs/AuE with the addition of dsDNA was observed, and the redox peak potentials shifted to more positive positions. These indicated that free Th molecules on the surface of electrode were embedded by dsDNA and dsDNA inhibited the redox reaction of Th due to the intercalation of Th between two successive base pairs of dsDNA as the predominant interaction mode (Hecht et al, 2004;Rohs et al, 2000), resulting in the decrease of the redox peak currents. In order to verify the interaction between Th and dsDNA, AFM characterization was performed.…”
Section: Interaction Of Dsdna With the Immobilized Thmentioning
confidence: 97%
“…Electroactive Th is an easy available cationic phenothiazine dye, which can bind strongly to dsDNA through intercalation (Du et al, 2005;Gong et al, 2008;Hecht et al, 2004;Ye et al, 2003), so it can be used as an intercalator to design electrochemical biosensors for the detection of DNA.…”
Section: Introductionmentioning
confidence: 99%